Blocking IP3 signal transduction pathways inhibits melatonin-induced Ca2+ signals and impairs P. falciparum development and proliferation in erythrocytes. (June 2018) - Pecenin, Mateus Fila; Borges-Pereira, Lucas; Levano-Garcia, Julio; Budu, Alexandre; Alves, Eduardo; Mikoshiba, Katsuhiko; Thomas, Andrew; Garcia, Celia R.S.
Graphical abstract: Highlights: Higher concentrations of DPB162-AE and DPB163-AE block the melatonin-induced [Ca 2+ ]cyt increase and SOCE in P. falciparum . P. falciparum SOCE is not activated in the same way as mammalian cells. DPB162-AE and DPB163-AE affect the development of the intraerythrocytic parasites and invasion of new RBCs. Melatonin does not stimulate SOCE in P. falciparum . Melatonin signaling pathway seems to be a potential target for the development of antimalarial drugs. Abstract: Inositol 1, 4, 5 trisphosphate (IP3 ) signaling plays a crucial role in a wide range of eukaryotic processes. In Plasmodium falciparum, IP3 elicits Ca 2+ release from intracellular Ca 2+ stores, even though no IP3 receptor homolog has been identified to date. The human host hormone melatonin plays a key role in entraining the P. falciparum life cycle in the intraerythrocytic stages, apparently through an IP3 -dependent Ca 2+ signal. The melatonin-induced cytosolic Ca 2+ ([Ca 2+ ]cyt ) increase and malaria cell cycle can be blocked by the IP3 receptor blocker 2-aminoethyl diphenylborinate (2-APB). However, 2-APB also inhibits store-operated Ca 2+ entry (SOCE). Therefore, we have used two novel 2-APB derivatives, DPB162-AE and DPB163-AE, which are 100-fold more potent than 2-APB in blocking SOCE in mammalian cells, and appear to act by interfering with clustering of STIM proteins. In the present work we report that DPB162-AE and DPB163-AE block the [Ca 2+ ]cyt rise in response to melatonin in P. falciparum, but only at high concentrations. These compounds also block SOCE in the parasite at similarly high concentrations suggesting that P. falciparum SOCE is not activated in the same way as in mammalian cells. We further find that DPB162-AE and DPB163-AE affect the development of the intraerythrocytic parasites and invasion of new red blood cells. Our efforts to episomally express proteins that compete with native IP3 receptor like IP3 -sponge and an IP3 sensor such as IRIS proved to be lethal to P. falciparum during intraerythrocytic cycle. The present findings point to an important role of IP3 -induced Ca 2+ release in intraerythrocytic stage of P. falciparum.